2022
DOI: 10.3390/foods11071004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Fermented Soy Sauce on Quality Characteristics of Pork Patties during Refrigerated Storage

Abstract: This study aimed to determine whether fermented soy sauce has a mutually synergistic effect on the quality and storage properties of pork patties, and to investigate the effects on the availability and physicochemical properties of various taste ingredients of soy sauce, a traditional Korean food ingredient. The experimental groups were as follows: Control (−): No additives; Control (+): 0.1% ascorbic acid; T1: 1% fermented soy sauce; T2: 3% fermented soy sauce; T3: 5% fermented soy sauce. No significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(65 reference statements)
3
3
0
Order By: Relevance
“…The improvement in textural properties of chicken meatballs may be due to the addition of oil to the product that reduced the strength of protein-gel mixture. The results were in complete agreement with the findings of Thomas et al [68] and Kim et al [69] in their experiments on the effect of fermented bamboo shoot mince on the quality of pork nuggets and the effect of soy sauce on quality of pork patties, respectively. Tomović et al [70] also observed improved instrumental textural qualities of dry fermented sausage upon the addition of essential oil.…”
Section: Effect Of Beo On Textural Properties Of Meatballssupporting
confidence: 92%
See 2 more Smart Citations
“…The improvement in textural properties of chicken meatballs may be due to the addition of oil to the product that reduced the strength of protein-gel mixture. The results were in complete agreement with the findings of Thomas et al [68] and Kim et al [69] in their experiments on the effect of fermented bamboo shoot mince on the quality of pork nuggets and the effect of soy sauce on quality of pork patties, respectively. Tomović et al [70] also observed improved instrumental textural qualities of dry fermented sausage upon the addition of essential oil.…”
Section: Effect Of Beo On Textural Properties Of Meatballssupporting
confidence: 92%
“…The results are also in accordance with the findings of various researchers [63,70,73]. The slightly higher yellowness (b*) values of treated products may be attributed to the oil base and antioxidants present in BEO [69].…”
Section: Effect Of Beo On Color Values Of Meatballssupporting
confidence: 91%
See 1 more Smart Citation
“…Sensory Evaluation. Sensory evaluation was measured by referring to the method used by Kim et al [26]. The sample was baked in a frying pan heated using a portable butane stove (DYC-3000, Daeyang, Busan, Korea) at the same intensity for 3 minutes and 30 seconds on each side and then cooled down at room temperature for 1 hour.…”
Section: Manufacturing Of Pattiesmentioning
confidence: 99%
“…CS-g-GA and CS-g-PA treatments delay the oxidation of proteins and amino acids and prolong the sea-bass shelf life by 6 days. According to a recent study conducted by Cho et al (2020), sauce pretreatment effectively reduces protein and lipid oxidation in grilled pork cakes, as soy sauce contains a large concentration of flavonoids and short peptides with antioxidant properties (Kim et al, 2022). Therefore, during the processing of meat products, it is beneficial to use an optimum proportion of sauce to reduce protein and lipid oxidation, and the formation of dityrosine.…”
Section: Adding Exogenous Antioxidants and Plant Extracts To Inhibit ...mentioning
confidence: 99%